2012
DOI: 10.1590/s1516-635x2012000200009
|View full text |Cite
|
Sign up to set email alerts
|

The effects of a combination of garlic, oyster mushroom and propolis extract in comparison to antibiotic on growth performance, some blood parameters and nutrients digestibility of male broilers

Abstract: A study was conducted to evaluate the combined effects of garlic, oyster mushroom and propolis extract on the growth performance, organ weights, antibody response to Newcastle Disease Virus (NDV), serum lipid concentrations and nutrient digestibility of male broilers. A total of 192 day old chicks (Ross 308) were randomly assigned to 3 treatments with 4 replications (16 birds per replication). Experimental treatments were a maize- soybean based diet as control, control diet supplemented with a combination of g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
30
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(39 citation statements)
references
References 23 publications
9
30
0
Order By: Relevance
“…Also, (Ghisalberti, 1979) reported the propolis has improved the broiler feed intake, this is due because the propolis content high amount of the fl avonoids. The present fi ndings show that the feed conversion ratio (FCR) in the experimental groups was improved compared to the control group, this results inagreement with (Botsoglou et al, 2004;Seven et al, 2008;Pourali et al, 2010;Tekeli et al, 2011;Daneshmand et al, 2012) who was found that the propolis increased the (FCR) on broiler chickens. The reason which led propolis to the improve the growth performance on the broiler because, the propolis has improve the digestive utilization of iron and the regeneration effi ciency of haemoglobin, especially during recovery from an anaemic syndrome, on other hand propolis has a positive eff ect on phosphocalcic metabolism and maintain an appropriate level of magnesium metabolism and improvement in the digestive utilization of these minerals (Haro et al, 2000).…”
Section: Resultssupporting
confidence: 74%
“…Also, (Ghisalberti, 1979) reported the propolis has improved the broiler feed intake, this is due because the propolis content high amount of the fl avonoids. The present fi ndings show that the feed conversion ratio (FCR) in the experimental groups was improved compared to the control group, this results inagreement with (Botsoglou et al, 2004;Seven et al, 2008;Pourali et al, 2010;Tekeli et al, 2011;Daneshmand et al, 2012) who was found that the propolis increased the (FCR) on broiler chickens. The reason which led propolis to the improve the growth performance on the broiler because, the propolis has improve the digestive utilization of iron and the regeneration effi ciency of haemoglobin, especially during recovery from an anaemic syndrome, on other hand propolis has a positive eff ect on phosphocalcic metabolism and maintain an appropriate level of magnesium metabolism and improvement in the digestive utilization of these minerals (Haro et al, 2000).…”
Section: Resultssupporting
confidence: 74%
“…stated that 5% F. velutipes mycelium did not improve feed intake in broilers, which was similar to the results of the present study with respect to feed intake. Another study by Daneshmand et al . found that the inclusion of oyster mushroom, garlic and propolis extract decreased the final body weight and BWG of birds.…”
Section: Discussionmentioning
confidence: 96%
“…Hong-Gu et al (2014) found that fermented F. velutipes mycelium had no significant effects on egg production in laying hens. In addition, Daneshmand et al (2012) reported that dietary inclusion of oyster mushroom, garlic, and propolis extract had no effects on broiler bird's body weight gain. In contrast by the author Hong-Gu et al 2014found that F. velutipes mycelium could improve egg size, egg mass, and FCR.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, feed additives originated from plants can stimulate the digestive functions and therefore could be used in poultry rations as feed additives (Mahanta et al, 2017). In contrast with Daneshmand et al (2012) reported that inclusion of oyster mushroom and antibiotic treatments could not affect protein and organic matter retention in broiler. These differences might be associated with mushroom type, mushroom parts, bird's strain, and mushroom inclusion levels in the experimental diets compared with the current study.…”
Section: Apparent Nutrient Retentionmentioning
confidence: 99%